David Kasner, MD, and the Road to Pars Plana Vitrectomy - Christopher F. Blodi (Ophthalmology and Eye Diseases, 2016)
David Kasner, MD (1927–2001), used his extensive dissections of eye bank eyes and experiences in teaching cataract surgery to resident physicians to realize that excision of vitreous when present in the anterior chamber of eyes undergoing cataract surgery was preferable to prior intraoperative procedures. Noting that eyes tolerated his maneuvers, he then performed planned subtotal open-sky vitrectomies; first on a traumatized eye in 1961, then on two eyes of patients with amyloidosis (1966–1967). The success of these operations was noted by others, most particularly Robert Machemer, MD. Kasner's work directly led to further surgical developments, including closed pars plana vitrectomy.